The Influence of Price Perception, Location and Service Quality on Customer Satisfaction of Taman Melati Margonda Apartment Through Rental Decision (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to analyze the influence of Price Perception, Location and Service Quality on Customer Satisfaction of the Taman Melati Margonda Apartment (KTMM) through a Rental Decision. Sources and research data using primary data in the form of a questionnaire, the research data was given to 150 respondents. Sampling research using Non-Probability Sampling with purposive sampling method. The analysis technique used is STATA-17. The results of the study concluded 1) Price Perception has a positive and not significant effect on Rental Decision; 2) Location has a positive and significant effect on Rental Decision; 3) Service Quality has a positive and significant influence on Rental Decision; 4) Price Perception has a negative and insignificant effect on Customer Satisfaction; 5) Location has a positive and insignificant effect on Customer Satisfaction; 6) Service Quality has a positive and significant effect on Customer Satisfaction; 7) Rental Decision failed to mediate the effect of Price Perception on Customer Satisfaction; 8) Rental Decision succeeded in mediating the effect of Location on Customer Satisfaction; 9) Rental Decision succeeded in mediating the effect of Service Quality on Customer Satisfaction; and 10) Rental Decision has a positive and significant effect on Customer Satisfaction.